A Reduction in Dosage of Acitretin to 17.5 mg/day Maintains Efficacy While Improving Tolerability. Issue 2 (June 2014) - Frankel, Amylynne J.; Ormerod, Jennifer; Lebwohl, Mark
Background: Oral acitretin 25 mg/day combined with a phototherapy regimen is a standard treatment for severe plaque-type psoriasis. Retinoid-related adverse events include alopecia, dry mucus membranes, pruritus, photosensitivity, elevation of liver enzymes, elevation of serum triglycerides and cholesterol and decrease of HDL, arthralgias, myalgias, eye irritation, blepharitis, photophobia, conjunctivitis, headaches, nausea, and anemia. Objective: This single-center open label study evaluated the efficacy and tolerability of a reduced acitretin dose in patients with severe plaque-type psoriasis undergoing phototherapy treatment who were experiencing at least one retinoid-related adverse event. Results: Of patients treated with 17.5 mg/day of acitretin, 89% demonstrated improved or comparable psoriasis area-and-severity index scores at week 12; 79% showed improvement in adverse events reported at baseline through week 12. Conclusion: There is a role for a lower dose of acitretin in patients who are experiencing retinoid-related side effects and who are stabilized on a phototherapy regimen.